2003
DOI: 10.1002/aic.690490317
|View full text |Cite
|
Sign up to set email alerts
|

Performance of immobilized photocatalytic reactors in continuous mode

Abstract: ) A packed-bed PBR , fiber FR , membrane MR , and tubular TR photocatalytic reactor ha®e been modeled to compare their performance on a pilot scale. The influence of radial dispersion in the PBR and mass-transfer limitation in the PBR, FR, and TR has been taken into account. The oxygen concentration in the liquid has a large influence on the performance and, therefore, air or pure oxygen should be added. The MR and PBR ha®e a better performance than the TR and FR. Only a small degree of mass-transfer limitatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 59 publications
2
14
0
2
Order By: Relevance
“…A literature review of reactor configurations tabulating photocatalytic research using slurry reactors and immobilised catalyst reactors can be found in [9], while a literature review tabulating methods of immobilisation of TiO 2 and support substrates coated can be found in [10,11]. Some researchers have reported that the efficiency of the slurried photocatalyst is larger than the supported form [8,10,12] while others have reported that the catalytic activity of TiO 2 is not affected when it is immobilised [13].…”
Section: Introductionsupporting
confidence: 40%
“…A literature review of reactor configurations tabulating photocatalytic research using slurry reactors and immobilised catalyst reactors can be found in [9], while a literature review tabulating methods of immobilisation of TiO 2 and support substrates coated can be found in [10,11]. Some researchers have reported that the efficiency of the slurried photocatalyst is larger than the supported form [8,10,12] while others have reported that the catalytic activity of TiO 2 is not affected when it is immobilised [13].…”
Section: Introductionsupporting
confidence: 40%
“…Various studies have identified the existence of mass transfer limitations in many immobilized systems, such as tubular reactors [7], [8], annular reactors [9]- [11], rotating disc reactors [9], [12], and packed-bed reactors [7], [13], among others [14]. A commonly used model equation derived from first principles is a Langmuir-type equation based on volumetric flowrate Q [15], [16]:…”
Section: Introductionmentioning
confidence: 43%
“…Various studies have identified the existence of mass-transfer limitations in many immobilized systems, such as tubular reactors [7][8], annular reactors [9][10][11], rotating disc reactors [9,12], and packed-bed reactors [7,13], among others [14]. A commonly used model equation derived from first principles is a Langmuir-type equation based on volumetric flowrate Q [15][16]:…”
Section: Introductionmentioning
confidence: 43%